Open source marketing: Camel cigarette brand marketing in the "Web 2.0" world. Issue 3 (11th February 2009) - Freeman, B; Chapman, S
Abstract : Background: The international trend towards comprehensive bans on tobacco advertising has seen the tobacco industry become increasingly innovative in its approach to marketing. Further fuelling this innovation is the rapid evolution and accessibility of web-based technology. The internet, as a relatively unregulated marketing environment, provides many opportunities for tobacco companies to pursue their promotional ambitions. Methods: In this paper, "open source marketing" is considered as a vehicle that has been appropriated by the tobacco industry, through a case study of efforts to design the packaging for the Camel Signature Blends range of cigarettes. Four sources are used to explore this case study including a marketing literature search, a web-based content search via the Google search engine, interviews with advertising trade informants and an analysis of the Camel brand website. Results: RJ Reynolds (RJR) has proven to be particularly innovative in designing cigarette packaging. RJR engaged with thousands of consumers through their Camel brand website to design four new cigarette flavours and packages. While the Camel Signature Blends packaging designs were subsequently modified for the retail market due to problems arising with their cartoon-like imagery, important lessons arise on how the internet blurs the line between marketing and market research. Conclusions: Open source marketing has the potential to exploit advertising ban loopholes and stretch legal definitions in order to generate positive word of mouth about tobacco products. There are also lessons in the open source marketing movement for more effective tobacco control measures including interactive social marketing campaigns and requiring plain packaging of tobacco products.